Effects of moderate dietary manipulations on swim performance and on blood lactate-swimming velocity curves - Reilly, T.; Woodbridge, V. (International Journal of Sports Medicine, 1999)
Zielstellung: Untersuchung des Einflusses von Ernährungmanipulierung auf die Schwimmleistung und die Beziehung zwischen Blutlaktat und Schimmgeschwindigkeit.